Europejscy Poszukiwacze czy Alterkontestatorzy - kolejne ogniwo wymiany pokoleń? - Wrzesień, Witold (Wydawnictwo Naukowe UAM, 2005)
When we deal with the generation change process we always observe, explore and try to explain features of the relations between older generation, fighting for preservation of their privileged position and younger generation. more or less consciously trying to change the existing status quo. The presented article is an attempt at first, harsh description of the probable next link of generation change process - the new generation group in Poland, which I call European Searchers.
European searchers or alterdissenters - next link in the generation change process?